ENVIRONMENTAL COMMUNICATION IN ONLINE MEDIA: STRATEGIES FOR DISSEMINATION OF GREEN ECONOMY VALUES BY LOCAL GREEN COMMUNITIES - Dino Arya Sukma; Irfandi Fahla; Eko Purwanto (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2025)
The escalating ecological crisis caused by climate change, pollution, and resource depletion demands urgent and transformative responses through a transition to a green economy. The green economy is viewed as a strategic solution to achieve sustainability and economic resilience by promoting responsible patterns of production and consumption. In this context, environmental communication plays a crucial role in disseminating sustainability values to the public, particularly through online media, which offers wide reach and interactive engagement. Local green communities, as grassroots actors, actively contribute to spreading green economic values by using digital communication strategies. This study aims to examine how local green communities use online media to convey environmental messages and raise public awareness of the green economy. Using a qualitative approach, this research seeks to contribute to the development of effective and contextual environmental communication strategies that support the broader transition toward sustainability.